IMPROVING SUGARCANE STEM LENGTH THROUGH BIPARENTAL CROSSING FOR HIGHER SUGARCANE YIELD AND SUGAR YIELD - Djumali; Herwati A.; Purwati R.D.; Riajaya P.D.; Machfud M.; Supriyono; Yulaikah S. (Russian Journal of Agricultural and Socio-Economic Sciences)
Sugar productivity could be increased by increasing sugarcane stem length. This study aims to produce better stem length and weight of crossed clones with higher sugar productivity than the SIL 04 clone. The study took place in Glugur of Ngenep Village, Karangploso District, Malang Regency of East Java Province, Indonesia, from October 2022 to October 2023. As many as 18 potential clones from biparental crossing (SIL 04 x (6535, PS 881 and BL)) with AS3 (21/5/..), AS 5 (21/9/..), MLG 18 (21/25/..) and 31228 (21/46/..), and one variety of SIL 04 were arranged in a Randomized Block Design with 2 replications. The results showed that clones 5/21/11 and 9/21/36 produced stem lengths of 120.85 and 74.01%, weight of 94.99 and 34.44%, sugarcane yield of 44.98 and 39.69%, and sugar yield of 20.42, which was 26.39% higher than SIL 04 (114.22 cm, 31.33 mm, 944.21 g stem-1, 82.41 t ha-1, and 10.04 ha-1). Improvements in sugar yield in crossed clones occurred through improvements in sugarcane yield (75.77%). Improvements in sugarcane yield occurred through improvements in stem weight (75.78%). Improvements in stem weight occurred through improvements in stem length (56.61%).